A DNP-supported solid-state NMR study of carbon species in fluid catalytic cracking catalysts. Issue 28 (22nd March 2017) - Mance, Deni; van der Zwan, Johan; Velthoen, Marjolein E. Z.; Meirer, Florian; Weckhuysen, Bert M.; Baldus, Marc; Vogt, Eelco T. C.
Abstract : Solid-state NMR techniques supported by EPR and SEM-EDX enable spatial speciation of carbon deposits in commercial fluid catalytic cracking catalysts. Abstract : A combination of solid-state NMR techniques supported by EPR and SEM-EDX experiments was used to localize different carbon species (coke) in commercial fluid catalytic cracking catalysts. Aliphatic coke species formed during the catalytic process and aromatic coke species deposited directly from the feedstock respond differently to dynamic nuclear polarization signal enhancement in integral and crushed FCC particles, indicating that aromatic species are mostly concentrated on the outside of the catalyst particles, whereas aliphatic species are also located on the inside of the FCC particles. The comparison of solid-state NMR data with and without the DNP radical at low and ambient temperature suggests the proximity between aromatic carbon deposits and metals (mostly iron) on the catalyst surface. These findings potentially indicate that coke and iron deposit together, or that iron has a role in the formation of aromatic coke.